The Relationship Between ADAMTS13 Activity and Overall Cerebral Small Vessel Disease Burden: A Cross-Sectional Study Based on CSVD - Sun, Wenbo; Luo, Yufan; Zhang, Shufan; Lu, Wenmei; Liu, Luqiong; Yang, Xiaoli; Wu, Danhong (Frontiers in Aging Neuroscience, 2021)
Objectives: This study aimed to investigate the association between plasma VWF level, ADAMTS13 activity and neuroimaging features of Cerebral Small Vessel Disease (CSVD), including the CSVD neuroimaging markers and the overall cerebral small vessel disease (CSVD) burden. Methods: CSVD patients admitted to our hospital from 2016 to 2020 were recruited. Plasma VWF level and ADAMTS13 activity were measured. The overall effect of CSVD on the brain was described as a validated CSVD score. We evaluated the association between VWF levels, ADAMTS13 activity and the increasing severity of CSVD score by the logistic regression model. Results: 296 patients were enrolled into this study. the mean age of the sample was 69.0 years (SD 7.0). The mean VWF level was 1.31 IU/mL , and the ADAMTS13 activity was 88.01 (SD 10.57). In multivariate regression analysis, lower ADAMTS13 activity and higher VWF level was related with white matter hyperintensity (WMH) [β = -7.31; 95%confidence interval (−7.31, -6.47); p＜0.01; β = 0.17; 95%confidence interval (0.11, 0.23); p＜0.01], Subcortical infarction (SI) [(β = -9.22; 95%CI (-11.37,-7.06); p＜0.01); β = 0.21; 95%confidence interval (0.15, 0.27); p＜0.01] independently, but not CMB [(β = −2.3; 95%CI(−4.95, 0.05); p = 0.22); β = 0.02; 95%confidence interval (-0.05, 0.08); p=0.63].Furthermore, ADAMTS13 activity was independently negatively correlated with the overall CSVD burden (Odd Ratio=21.33; 95%CI(17.46,54.60); p<0.01) after adjustment for age, history of hypertension, and current smoking. Conclusions: Reducing ADAMTS13 activity change is related to white matter hyperintensity, subcortical infarction, but not with cerebral microhemorrhage. In addition, ADAMTS13 may have played an essential role in the progression of CSVD.